対側オトガイ部の知覚異常が早期症状と疑われたびまん性大細胞型B 細胞性リンパ腫の1例 - 南川, 勉; 古森, 孝英; 辻, 和志; 明石, 昌也; 高端, 大希; 高橋, 佑輔 (日本口腔外科学会雑誌, 2016)
Diffuse large B cell lymphoma (DLBCL) is a typical malignant tumor classified as a non-Hodgkin lymphoma. Rare cases in which DLBCL is a ssociated with diverse neurological symptoms such as chin numbness and ophthalmoplegia have been reported previously. We describe a case of paresthesia of the contralateral mental region suspected to be an early symptom of DLBCL. The patient was a 73-year-old woman. Her chief complaints were desensitization and sharp pain in the lips and the right submandibular region. During treatment for these symptoms, the left submandibular region became acutely swollen. She underwent a biopsy of a mass lesion in left mandibular molar gingiva. The histopathological diagnosis was DLBCL. Eight cycles of R-CHOP treatment were administered in a hematology unit in our hospital. Although a reduction in the tumor was confirmed by on combined positron-emission tomography and computed tomography performed after R-CHOP, the paresthesia of both mental regions persisted. She is currently under follow-up observation in our department.